2016
DOI: 10.1139/cjce-2015-0114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating disability management in the Manitoban construction industry for injured workers returning to the workplace with a disability

Abstract: ABSTRACT:The poor safety record of the construction industry raises concerns about the extent to which it is able to integrate workers disabled as a result of a workplace injury back to the workplace. A review of the literature indicates there is little empirical evidence about the status of disability management (DM) in the Canadian construction industry, specifically with respect to injured construction workers returning to the workplace with a disability. To address this limitation, a web-based survey was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 10 publications
7
23
1
1
Order By: Relevance
“…One technique provided to the SLPC managers was to simply approach a new employee at the end of the shift and asking how their shift went and if there was anything the new employee thought could be improved. Assuming the feedback from the new employees are addressed in some way, this should make the employee feel valued and acknowledged as well as allow them to be an active part of making their work life better (Hammerback et al, 2015;Winter et al, 2016).…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…One technique provided to the SLPC managers was to simply approach a new employee at the end of the shift and asking how their shift went and if there was anything the new employee thought could be improved. Assuming the feedback from the new employees are addressed in some way, this should make the employee feel valued and acknowledged as well as allow them to be an active part of making their work life better (Hammerback et al, 2015;Winter et al, 2016).…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…This research also builds on the earlier work by Winter et al (2015) aiming to assess DM within the Manitoban construction industry using a Web-based survey of 88 construction organizations, and representing the only Canadian work conducted to date about the topic. The research showed that only 4 per cent of surveyed organizations employed 5 per cent or more disabled workers.…”
Section: Disability Managementmentioning
confidence: 99%
“…Surveyed organizations found musculoskeletal (MSI) injuries to be the most common disability encountered, followed by physical mobility and hearing impairments. Winter et al (2015) also identified the lack of suitable modified or alternate work to be the most important barrier to DM yet identified the provision of this work as the most common practice implemented by them, raising questions about this work’s suitability to disabled workers. This research builds on this by proposing and validating DM practices, which takes into account the unique characteristics of the construction industry.…”
Section: Disability Managementmentioning
confidence: 99%
See 2 more Smart Citations